2008
DOI: 10.1097/rli.0b013e31815a251b
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Streptavidin-Coated Cyanoacrylate Microbubbles Designed for Molecular Ultrasound Imaging

Abstract: The pharmacokinetic behavior of streptavidin-coated cyanoacrylate MBs has been studied. In this context, the low amount of MBs in tumors after >5 minutes is beneficial for specific targeting of angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 25 publications
4
55
0
1
Order By: Relevance
“…In this study, we were able to show the specificity of targeted microbubbles, which accumulated significantly within tumor vessels compared with unspecific ones. In a previous study about the pharmacokinetic behavior of cyanoacrylate microbubbles, we were further able to show that 1.5 min after injection the blood concentrations of microbubbles in mice already decreased to less than 2% of the maximum peak enhancement (24). Commensurate with these findings, this study also found no relevant replenishment of microbubbles in control scans following the diagnostic scan done 7 min after microbubble injection.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, we were able to show the specificity of targeted microbubbles, which accumulated significantly within tumor vessels compared with unspecific ones. In a previous study about the pharmacokinetic behavior of cyanoacrylate microbubbles, we were further able to show that 1.5 min after injection the blood concentrations of microbubbles in mice already decreased to less than 2% of the maximum peak enhancement (24). Commensurate with these findings, this study also found no relevant replenishment of microbubbles in control scans following the diagnostic scan done 7 min after microbubble injection.…”
Section: Discussionsupporting
confidence: 70%
“…Subsequently, 50 AL of 0.9% NaCl were injected to clear the catheter from microbubbles. Imaging was done 7 min after microbubble administration as suggested by prior studies in which timing variables had been optimized (18,24). The initial ultrasound scan of the whole tumor volume was followed by three control scans.…”
Section: Synthesis and Characterization Of Target-specific Microbubblesmentioning
confidence: 99%
“…This plateau can be explained by the heterogeneous in vivo stability of the microbubbles within one charge (e.g., due to differences in size, wall thickness, and wall homogeneity; ref. 30). The sum of injected particles causes the initial peak of the enhancement curve.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound contrast agents containing encapsulated microbubbles are mainly used to increase the diagnostic imaging of tumors. McCarville et al [18] showed that gray-scale US measurements of microbubble contrast agent flow can be used to detect the functional consequences of antiangiogenic therapy for tumors and to assess angiogenesis inhibitors that act through different mechanisms [19][20][21][22][23] . Recently, lymphangiogenesis has become a new research frontier [10] .…”
Section: Discussionmentioning
confidence: 99%